Jaw-Closing Oromandibular Dystonia Induced by Speaking in a Patient with Systemic Sclerosis - Hasan, ATM Tanveer; Abda, Syed Jamil; Yesmin, Sabrina; Ahmed, Shamim (Journal of Enam Medical College, 2018)
Oromandibular dystonia is a rare form of focal dystonia caused by involuntary spasms of masticatory, lingual and pharyngeal muscles. Here we describe a 53-year-old edentulous woman with systemic sclerosis who presented with dysarthria due to bilateral contraction of her masseter muscles during speaking. An anticholinergic medication was prescribed instead of botulinum toxin injection. Her condition markedly improved after medication. We suspected that edentulosity caused an impairment of proprioception in the oral cavity leading to subsequent development of dystonia. J Enam Med Col 2018; 8(3): 170-173